Development and construction of a portable wind tunnel for investigating wind erosion through the application of photogrammetry techniques - Noredin Rostami; Maryam Rabbani; Saman Esmaeilbeigi; Kamyar Hassanpour; Mohammad Hossein Shahmoradi; Mohammad Najafishoa; Zahra Ghobadian; Masood Varshosaz; Mehdi Norianfar (Scientific Reports)
Abstract Climate change is one of the most crucial issues in human society such that if it is not given sufficient attention, it can become a great threat to both humans and the Earth. Due to global warming, soil erosion is increasing in different regions. Therefore, this issue will require further investigation and the use of new tools. In this paper, a portable wind tunnel was designed and built for wind erosion studies using photogrammetry, which is a novel technique. This instrument consists of a working section, a fan, a portable voltage source inverter to control its angular speed, and a honeycomb to straighten the air flow in the working section. The eroded volume of soil is measured using photogrammetry by producing two 3D models and point clouds before and after the soil erosion test and calculating their volume changes. The results show that a 0.175 mm check distance precision is achievable under convergent imaging and with sufficient number of accurate control points which this value indicates the discrepancy between the anticipated and measured lengths of all the check distances. In addition, the features of this portable wind tunnel guarantee its easy portability, and its transparency enables the measurement of the threshold friction velocity. Additionally, this instrument, as an invention, has been registered at the Intellectual Property Center of Iran.